Selective Adsorption of Cationic and Anionic Dyes using Ni/Al Layered Double Hydroxide Modified with Eucheuma cottonii - Sahrul Wibiyan; Idha Royani; Aldes Lesbani (Magister Program of Material Science Graduate School of Universitas Sriwijaya, 2024)
This study investigates the selective adsorption capabilities of Ni/Al Layered Double Hydroxide (LDH) modified with Eucheuma cottonii for the removal of cationic and anionic dyes from aqueous solutions. The primary objective was to evaluate the efficiency and selectivity of these modified adsorbents towards different dyes, including rhodamine-b, malachite green, methylene blue (cationic dyes), and direct yellow, methyl orange, direct green (anionic dyes). The modification process aimed to enhance the adsorption properties of LDHs, leveraging the natural adsorption capabilities of Eucheuma cottonii. Experimental results demonstrated significant differences in adsorption percentages among the tested dyes, with malachite green showing the highest adsorption efficiency among cationic dyes, indicating a strong affinity of the modified adsorbents towards cationic dyes. However, the ability to also adsorb anionic dyes suggests the dual-functionality of the modified LDHs, making them versatile agents for dye removal in water treatment applications.